Watched - Budhos, Marina Tamar (Wendy Lamb Books, 2016)
Far from the "model teen," Naeem moves fast to outrun the eyes of his hardworking Bangladeshi parents, their gossipy neighbors, and the other forms of surveillance in his immigrant neighborhood in Queens, but when his mistakes catch up with him and the police offer a dark deal, will Naeem be a hero or a traitor?